The WD40 gene family in recretohalophyte Limonium bicolor: genomic identification and functional analysis in salt gland development and salinity tolerance - Sun, Lu; Mu, Huiying; Tan, Yuqing; Wang, Baoshan; Wang, Xi; Yuan, Fang (Frontiers in Plant Science, 2025)
IntroductionDeveloping salt-tolerant crops is critical for utilizing saline soils in agriculture. Limonium bicolor, a recretohalophyte with epidermal salt glands, represents a valuable genetic resource for salt tolerance engineering. Although WD40 proteins are known regulators of plant stress responses, their roles in L. bicolor remain unexplored.MethodsWe performed a genome-wide analysis of WD40 genes in L. bicolor, including phylogenetic classification, subcellular localization prediction, cis-element analysis, and expression profiling during salt stress. Functional validation was conducted using virus-induced gene silencing (VIGS).ResultsAmong 367 identified WD40 genes (distributed across all chromosomes), Subfamily 6 was the largest. Two key members (Lb1G05968 and Lb3G17197, localized in cytoplasm) showed significant involvement in salt gland development and stress tolerance, as demonstrated by VIGS-induced phenotypic defects.DiscussionOur findings reveal the WD40 family's expansion in L. bicolor and its functional specialization in salt adaptation. The identified genes (e.g., Lb1G05968, Lb3G17197) provide targets for engineering salt-tolerant crops. This study establishes a foundation for further research on halophyte developmental genetics.